A brief historical overview of pronunciations of English in dictionaries - Lewis, Jack Windsor (Linguistica (Ljubljana), 2017)
The evolution of pronunciations in mainly British English dictionaries is traced from their beginnings, with accounts of certain neglected figures in the field. In the paper we discuss how representations of pronunciations have developed from being indicated by means of conventional spelling with the addition of marks and numbers to more sophisticated systems of phonetic notation. A significant feature of the twenty-first century is the addition of spoken pronunciations of the items.
Keywords: angleščina; English; izgovorjava; leksikografija; lexicography; slovarji; zgodovinski pregledi